2021
DOI: 10.1016/j.foodqual.2021.104300
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of food waste reduction behaviour in the household context

Abstract: Studies on the drivers of household consumer engagement in various food waste reduction strategies have been limited. We thus address this gap by developing a research model that utilises two well-known theories, namely, the Theory of Interpersonal Behaviour (TIB) and the Comprehensive Model of Environmental Psychology (CMEP), to explain food waste reduction behaviour in household consumers. The model hypothesises positive associations between emotional, social, and cognitive factors and food waste reduction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 121 publications
4
62
0
1
Order By: Relevance
“…It is essential to reduce FW by acting on the entire food chain, as generally considered also in several previous studies [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is essential to reduce FW by acting on the entire food chain, as generally considered also in several previous studies [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 94%
“…It is essential to reduce FW by acting on the entire food chain, as generally considered also in several previous studies [27][28][29][30][31][32][33]. When we talk about the food supply chain, we must consider it as a combination of interactions between farmers and consumers connected with different food processing and distribution companies [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…According to Attiq et al [55], the theory of planned behavior does not offer support in explaining the emotions related to food wastage, as suggested by the literature, such as Russell et al [53] and Filimonau et al [56]. Scholars have thus emphasized the need to explore other suitable theoretical approaches, such as the theory of interpersonal behavior, the comprehensive model of environmental psychology, and social practice theory [12,53,55]. Attiq et al [55] used the integration model of the theory of planned behavior and a comprehensive model of environmental psychology to explain food wastage reduction behavior in household consumers.…”
Section: Theoretical Background and The Research Gapmentioning
confidence: 99%
“…Scholars have thus emphasized the need to explore other suitable theoretical approaches, such as the theory of interpersonal behavior, the comprehensive model of environmental psychology, and social practice theory [12,53,55]. Attiq et al [55] used the integration model of the theory of planned behavior and a comprehensive model of environmental psychology to explain food wastage reduction behavior in household consumers. Their results showed that emotional (anticipated guilt), social (sense of community), and cognitive factors (awareness of consequences and environmental knowledge) were positively associated with food wastage reduction behavior [55].…”
Section: Theoretical Background and The Research Gapmentioning
confidence: 99%
See 1 more Smart Citation